2014
DOI: 10.1111/1574-6968.12519
|View full text |Cite
|
Sign up to set email alerts
|

Isolation ofStreptococcus tigurinus- a novel member ofStreptococcus mitisgroup from a case of periodontitis

Abstract: Streptococcus tigurinus is a new member of the Streptococcus viridians group and is closely related to Streptococcus mitis, Streptococcus pneumoniae, Streptococcus pseudopneumoniae, Streptococcus oralis, and Streptococcus infantis. The type strain AZ_3a(T) of S. tigurinus was originally isolated from a patient with infective endocarditis. Accurate identification of S. tigurinus is facilitated only by newer molecular methods like 16S rRNA gene analysis. During the course of study on bacteraemia and infective en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 30 publications
1
16
0
Order By: Relevance
“…in the HP(−) cancer group was more greater than the others (Table 2). The proportion of Streptococcus mitis group,2022 such as S. pseudopneumoniae, S. mitis, S. infantis, S. oralis , and S. tigurinus , in the HP(−) cancer group was more higher than in that of the HP(+) cancer group (antrum, 33.9 vs. 8.4, P = 0.076; body, 34.1 vs. 0.33, P = 0.009; Table 2). These results suggest a role of S. mitis in the gastric carcinogenesis despite the absence of HP.…”
Section: Resultsmentioning
confidence: 99%
“…in the HP(−) cancer group was more greater than the others (Table 2). The proportion of Streptococcus mitis group,2022 such as S. pseudopneumoniae, S. mitis, S. infantis, S. oralis , and S. tigurinus , in the HP(−) cancer group was more higher than in that of the HP(+) cancer group (antrum, 33.9 vs. 8.4, P = 0.076; body, 34.1 vs. 0.33, P = 0.009; Table 2). These results suggest a role of S. mitis in the gastric carcinogenesis despite the absence of HP.…”
Section: Resultsmentioning
confidence: 99%
“…S. tigurinus not only was detected in patients with periodontitis but also in individuals without periodontal diseases. 41,53 Earlier studies have demonstrated that S. mitis, which is the closest related species to S. tigurinus, is a predominant early colonizing species of dental biofilms. 54 Although S. mitis is not a potent inducer of immune responses, it can antagonize the capacity of A. actinomycetemcomitans (a key pathogen associated with the localized aggressive form of periodontitis occurring in younger individuals) to stimulate IL-8.…”
Section: Association Of S Tigurinus With Oral Infectionsmentioning
confidence: 99%
“…After the first isolates (AZ_3a [type strain, synonym DSM 24864], AZ_1-AZ_15) were described in Zürich, Switzerland, in 2012 [10], additional S. tigurinus isolates were found again in Switzerland (strain 1366 with small colony variants nos. 2425 and 2426), in Japan (two isolates of infective endocarditis [11]), in India (single isolate from the oral cavity of a periodontitis patient [12]), again in Switzerland (several isolates from the oral cavity [13], again in Japan (culture-negative endocarditis case [8] and one from bacteremia [14]), in Spain (endocarditis case [15]), in France (two endocarditis cases [16]), and in Washington, USA, where 14 isolates were recovered from numerous body sides, expanding the spectrum of associated diseases [17]. Up to November 2016, seven S. tigurinus genome sequences (strains AZ_3a, 1366, 2425, 2426, DGIIBVI and JPIBVI, UC5873) have been made accessible in GenBank [1820].…”
Section: Introductionmentioning
confidence: 99%